Interdisciplinary work at school with projects (Research, Society and Development, 2022)
The educational system currently requires methodologies that generate changes in teaching and learning, making the student the protagonist of the construction of their own knowledge. The Project Pedagogy proposed as interdisciplinary education, aims to work skills and abilities necessary for social transformation. The redefinition of the school environment is necessary to insert the school in this contemporary experience, the change in attitude transforms the school into a significant place for teaching and learning, involving the school community within its reality. The methodology used is documentary and bibliographic research, with a qualitative nature. The project pedagogy presented in this article works on three important moments: The stage of problematization, work development and synthesis, effectively contributing to the formation of the student's social and cognitive development. The educator is the mediator of all pedagogical work and students acquire knowledge with the opportunity to make the educational action more meaningful.